Kendala Dalam Pembelajaran Berbicara Di Jurusan Teknik Kelistrikan Kapal Universitas Ivet Tahun Akademik 2023/2024 - Wibowo, Rahmat Ari; Sulistyorini, Dwi (Marine Science and Technology Journal, 2025)
English as a foreign language instruction and learning in Indonesia. Speaking is one of the core abilities to be acquired in the process of teaching and learning English. Speaking serves as a crucial component of communication. Gaining proficiency in speaking English is essential for all students to be able to converse in the language. Speaking is a skill that both first and second language learners should focus on. The most crucial part of learning a second or foreign language is developing speaking abilities, and proficiency is determined by one's capacity to carry on a conversation in the target language (Nunan, 1995). The second problem is that learners complain that they cannot remember anything to say and they do not have any motivation to express themselves. This is supported by Rivers (1968) who thinks that learners often have nothing to say probably because their Lecturers had selected a topic that is not appropriate for them or they do have enough information about it. The method used in this research is descriptive quantitative. The data obtained from the test was analysed by Likert scale procedure indicated whether one strongly agree (SA), Agree (A), Undecided (U), Disagree (D), Strongly Disagree (SD) with each statement. The score was determine by summing the point of value of each statement. The technique of analyzed data in the research was used descriptive percentage. The technique was used asses variable of the research. The researcher classify their collect data from observation class and questionnaire, data collection from questionnaires is Likert Scale was used to assess and calculated data which obtain from questionnaires. Based on the findings and discussion, it could be concluded that there are some problems in speaking English by the fifth semester at Ship electrical engineering of Ivet University. The result of the study, there are some students’ problems in practicing speaking English. The problems students’ in practicing speaking English are inhibition, nothing to say, low or uneven participation and mother tongue used. It is because they do not master the three primary elements of speaking namely, vocabulary, grammar, and pronunciation